The impact of Internet-based healthcare derived from the COVID-19 pandemic on outpatients in a cardiology department - Liu, Jie; Fei, Yunhan; Gao, Ying; Meng, Yu; Huang, Dongxue; Zhao, Wenjuan; Xie, Keliang (Frontiers in Digital Health, 2025)
ObjectiveThis study examines the impact of a COVID-19 pandemic-derived online medical service on cardiovascular patient visits and assesses whether these services can ease the strain on medical resources.MethodThis study investigated the impact of the COVID-19 pandemic on cardiology services and hospital operations. We analyzed key primary medical indicators in cardiology, including outpatient visits, inpatient improvement rates, cure rates, and mortality rates, over three years from 2019 to 2021. Furthermore, the study assessed the influence of the development of Internet-based medical services on the treatment of cardiovascular disease. Specifically, we compared the changes in the number of outpatient visits in four categories of offline outpatient clinics in the Department of Cardiology during two phases: Phase I (1 February 2019 to 28 February 2020) and Phase II (1 March 2020 to 28 February 2021).ResultsCompared to the period before online services (T1), the second stage (T2) saw a significant decrease in total offline and general clinic visits. After the establishment of the online clinic, the third period (P3) showed a significant reduction in total offline, general, and senior clinic visits compared to the first period (P1), while vice-senior and VIP/international clinic visits increased. The number of online clinic visits and VIP/international clinic visits continued to rise. Online consultations had the highest proportion (55.9%), while prescriptions and examinations had the lowest (3.3%), although they showed a gradually increasing trend. After the implementation of the online clinic, the improvement rate of patients' conditions increased and the mortality rate decreased.ConclusionSince the advent of online medical services, cardiovascular patients have increasingly opted for online diagnosis and treatment. Since March 2021, the online outpatient service has driven the overall growth in hospital outpatient numbers while maintaining medical quality. The primary use of the online medical service is for consultations, which shortens medical time and reduces implicit costs for patients.